Knowledge in the Investigation of A-to-I RNA Editing Signals - Nigita, Giovanni; Alaimo, Salvatore; Ferro, Alfredo; Giugno, Rosalba; Pulvirenti, Alfredo (Frontiers in Bioengineering and Biotechnology, 2015)
RNA editing is a post-transcriptional alteration of RNA sequences that is able to affect protein structure as well as RNA and protein expression. A-to-I (Adenosine-to-Inosine) RNA editing is the most frequent and common post-transcriptional modification in the human, where adenosine (A) deamination produces its conversion into inosine (I), which in turn is interpreted by the machinery translation and splicing as guanosine (G). The disruption of the editing machinery has been associated in various human diseases such as cancer or neurodegenerative diseases. This biological phenomenon is catalyzed by members of the Adenosine Deaminase Acting on RNA (ADAR) family of enzymes and occurs only on dsRNA structures. Although the enormous efforts made in the last years, the real biological function underlying of such a phenomenon as well as the features of the substrate of the ADAR still remain unknown. In this work we summarized the major computational aspects on predicting and understanding RNA editing events. We also investigate the detection of short motifs sequences characterizing RNA editing signals and the use of a logistic regression technique to model a predictor of editing site events. The last, called AIRlINER, is available as a web app at: http://alpha.dmi.unict.it/airliner/. Results and comparisons with the existing methods encourage our findings on both aspects.